Analysis of Factors Affecting the Development of Micro Enterprises in Samadua District - Raihan Nirwana; Rollis Juliansyah; Liasulistia Ningsih (Outline Journal of Economic Studies, 2026)
Purpose: This study aims to examine the influence of capital, marketing, skills, and training on the development of microenterprises in Samadua Subdistrict, South Aceh Regency. Methods: The study employs a quantitative approach with 100 micro-business owners as respondents. Data analysis was conducted using multiple linear regression. Results: The results indicate that, individually, capital, marketing, and training do not have a significant effect on the development of micro-businesses. Conversely, skills have a significant effect because they are directly related to the ability to operate and manage a business. The lack of significance of capital is attributed to the limited capital available to business owners, marketing efforts that remain rudimentary, and training programs that are primarily implemented at the regency level, thereby failing to reach microbusiness owners in the sub-district evenly. Simultaneously, all variables have a significant effect on the development of microbusinesses. Conclusions: This study concludes that skills are the most influential factor in the development of microenterprises in Samadua Subdistrict because they directly support business management and operational effectiveness. Originality/value: This study provides empirical evidence on the development of microenterprises in Samadua Subdistrict, South Aceh Regency, an area that has received limited academic attention.